2011
DOI: 10.4274/jcrpe.415
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Control in Children and Adolescents with Insulin-Dependent Diabetes Mellitus at

Abstract: Objective: Preventing long-term diabetic complications requires good metabolic control, especially in type 1 diabetes mellitus (T1DM). We describe the metabolic control of T1DM and the factors affecting it among children and adolescents attending the Pediatric Clinic at King Abdul-Aziz University Hospital. Methods: A retrospective cross-sectional study was conducted on T1DM children and adolescents who had attended the Pediatric Clinic at King Abdul-Aziz University Hospital from 2006 to 2010. Both clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In other words, SMBG frequency did not increase with the number of injections among patients in group 2A. The refusal of adolescent patients to increase monitoring frequency, as well as their reluctance to follow a strict diet and exercise more frequently, is commonly encountered in clinical practice [ 4 , 7 , 11 , 12 ]. We thus believe that the lack of good disease management caused poor glycemic control after 6 months of MDIs/CSII therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, SMBG frequency did not increase with the number of injections among patients in group 2A. The refusal of adolescent patients to increase monitoring frequency, as well as their reluctance to follow a strict diet and exercise more frequently, is commonly encountered in clinical practice [ 4 , 7 , 11 , 12 ]. We thus believe that the lack of good disease management caused poor glycemic control after 6 months of MDIs/CSII therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The Diabetes Control and Complications Trial (DCCT) and the follow-up Epidemiology of Diabetes Intervention and Complications Study (EDIC) confirmed that intensive insulin treatment could improve glycemic control, reducing or delaying the long-term complications of T1DM, with a persistent benefit [ 1 – 3 ]. Since these results were published, intensive insulin therapy has been widely applied in clinical practice, almost becoming the standard of care [ 4 6 ]. However, in contrast to the DCCT and EDIC findings, Holl et al [ 7 ] found that the use of intensive therapy did not improve glucose control in clinical practice in 17 European countries.…”
Section: Introductionmentioning
confidence: 99%
“…In the adolescent population, poor glycemic control, changing physiology, and behavioural and adherence issues can be causative factors in acute and chronic complications of T1DM (Al-Agha, Ocheltree, & Hakeem, 2011). However, daily self-monitoring of blood glucose, daily insulin injections, regular hemoglobin A1c (HgbA1c) measurements, and close monitoring of physical activity can aid in the reduction of T1DM-associated complications (Al-Agha et al, 2011;CDACPGEC, 2013).…”
Section: Complicationsmentioning
confidence: 99%